Assistance of Batik Tulis in Nurul Huda Islamic Boarding School Situbondo through E-Commerce to Improve Socio-Economic Levels - Yusuf Amrozi; Hanafi Adi Putranto; Faris Muslihul Amin; Tazkia Shabrina Az-Zahra (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Situbondo Regency is one of the regencies in East Java Indonesia that is thick with Madurese culture and its religious community. In this area, it is also the center of Islamic boarding schools. Interestingly, although in this regency is a pesantren base, there is one pesantren which is quite old and a pioneer in the development of the creative economy through a handicraft called batik (batik tulis). By using the participatory action research (PAR) approach, this community assistance aims to to visualize the reality of batik tulis as well as to build awareness in the pesantren community to adopt technology in marketing management, considering that problem lies in marketing. Through the support of E-Commerce system, the results of community assistance show that there are greater prospects in improving the socio-economic level of Islamic boarding schools in the creative economy business of batik tulis with supported by information technology